Magma plumbing for the 2014–2015 Holuhraun eruption, Iceland. (5th August 2016) - Geiger, Harri; Mattsson, Tobias; Deegan, Frances M.; Troll, Valentin R.; Burchardt, Steffi; Gudmundsson, Ólafur; Tryggvason, Ari; Krumbholz, Michael; Harris, Chris
Abstract: The 2014–2015 Holuhraun eruption on Iceland was located within the Askja fissure swarm but was accompanied by caldera subsidence in the Bárðarbunga central volcano 45 km to the southwest. Geophysical monitoring of the eruption identified a seismic swarm that migrated from Bárðarbunga to the Holuhraun eruption site over the course of two weeks. In order to better understand this lateral connection between Bárðarbunga and Holuhraun, we present mineral textures and compositions, mineral‐melt‐equilibrium calculations, whole rock and trace element data, and oxygen isotope ratios for selected Holuhraun samples. The Holuhraun lavas are compositionally similar to recorded historical eruptions from the Bárðarbunga volcanic system but are distinct from the historical eruption products of the nearby Askja system. Thermobarometry calculations indicate a polybaric magma plumbing system for the Holuhraun eruption, wherein clinopyroxene and plagioclase crystallized at average depths of ∼17 km and ∼5 km, respectively. Crystal resorption textures and oxygen isotope variations imply that this multilevel plumbing system facilitated magma mixing and assimilation of low‐δ 18 O Icelandic crust prior to eruption. In conjunction with the existing geophysical evidence for lateral migration, our results support a model of initial vertical magma ascent within the Bárðarbunga plumbing system followed by lateral transport of aggregated magma batches within the upper crust to the Holuhraun eruption site. Key Points: New petrological and geochemical data for the 2014–2015 Holuhraun fissure eruption Holuhraun lavas are compositionally similar to the Bárðarbunga volcanic system Multilevel magma plumbing beneath Bárðarbunga fed the Holuhraun eruption